Synchronization of Children's Rights in Indonesian Positive Law (Study of Synchronization of Children's Rights as Crime Perpetrators) - Usi Susanti; Gazali, Gazali; Lalu Muhammad Nurul Wathani (al-Afkar, Journal For Islamic Studies, 2025)
Children as the nation's next generation have an important role in national development. However, children involved in crime are often overlooked in legal protection. This research aims to explore the synchronization of the rights of children who commit crimes in Indonesian positive law, as well as analyzing the application of legal provisions by law enforcement officials. The research method used is normative juridical with a descriptive approach, involving the analysis of secondary data from legislation and jurisprudence. The results showed that there was a lack of conformity in the legal protection of child offenders, as well as the need for harmonization of regulations to ensure that children's rights were met. The recommendations of this study are the need for awareness-raising and more effective implementation of legal protection for children, as well as strengthening the role of society and government in supporting optimal child development.